ChemInform Abstract: A Versatile Synthesis of "Tafuramycin A": A Potent Anticancer and Parasite Attenuating Agent. Issue 48 (2nd December 2014) - El‐Deeb, Ibrahim M.; Rose, Faith J.; Healy, Peter C.; von Itzstein, Mark
Abstract The improved synthesis of tafuramycin A (I) includes a regioselective bromination step, a controlled aryl radical alkene cyclization to prevent dechlorination, and a new protection/deprotection method to avoid double bond reduction of the furan ring during deprotection of the benzyl group.